2003
DOI: 10.1128/aem.69.9.5693-5698.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Production of Paralytic Shellfish Toxin by Bacteria Associated with Dinoflagellates of the Portuguese Coast

Abstract: Paralytic shellfish toxins (PSTs) comprise a suite of potent neurotoxins that act by blocking sodium channels in nerve axons (3). These toxins may cause severe human poisoning upon consumption of contaminated shellfish. The production of PSTs by dinoflagellates has been thoroughly documented and confirmed worldwide. Strains of the dinoflagellates Alexandrium lusitanicum Balech and Gymnodinium catenatum Graham isolated from Portuguese waters have been shown by different detection methods to produce PSTs (1,6,7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Reports indicate that bacteria may produce ''phycotoxins'' autonomously (Simidu et al, 1990;Córdova et al, 2003) or be major contributors to toxin production in association with other organisms (Stewart et al, 1997;Hold et al, 2001a). However, conclusive evidence has been elusive (Baker et al, 2003), and Martins et al (2003) have reevaluated previous published reports of paralytic shellfish toxin production by bacteria associated with dinoflagellates.…”
Section: Introductionmentioning
confidence: 89%
“…Reports indicate that bacteria may produce ''phycotoxins'' autonomously (Simidu et al, 1990;Córdova et al, 2003) or be major contributors to toxin production in association with other organisms (Stewart et al, 1997;Hold et al, 2001a). However, conclusive evidence has been elusive (Baker et al, 2003), and Martins et al (2003) have reevaluated previous published reports of paralytic shellfish toxin production by bacteria associated with dinoflagellates.…”
Section: Introductionmentioning
confidence: 89%
“…This hypothesis has been investigated by numerous studies, though the results were conflicting [30,31,32,33,34]. Additionally, some of the methods used to measure bacterial metabolites have subsequently been shown to lack specificity, with compounds thought to be STX later being identified as chemical imposters [32,34]. …”
Section: Re-evaluation Of the Three Theories Of Stx Evolution In Dmentioning
confidence: 99%
“…There is no doubt that many cyanobacteria can autonomously produce PST compounds, and a plausible biosynthetic pathway has been recently described (Kellmann et al 2008), but the evidence for PST production by other heterotrophic bacterial groups is weaker. While a number of bacteria have been reported to produce toxins having chromatographic and biological activity similar to that of PST compounds (Kodama et al 1988, Gallacher et al 1997, Smith et al 2002, several studies have demonstrated that this activity can be attributed to compounds structurally unrelated to PSTs (Sato & Shimizu 1998, Baker et al 2003, Martins et al 2003. Alternatively, bacteria may be directly involved in dinoflagellate PST biosynthesis by supplying precursor compounds or synthesizing key intermediates in the biosynthetic pathway (Gallacher & Smith 1999).…”
Section: Introductionmentioning
confidence: 99%